Estudo da deformação permanente de três solos típicos de subleitos rodoviários de Santa Maria - RS - Zago, João Paulo (2016)
Studies conducted in 2016 show that 58% of the highways in Brazil presents any deficiency in the pavement, signaling or in its geometry. These deficiencies are, on average, the cause for about 6% of the accidents and for the increase of the operational cust by 91,6%. Among them we can stress the permanent deformation, the so called wheel tracks, which is harmful to the dynamic of the loads, to the comfort provided by the pavement, increasing its risk. To the correct design of the pavement it is very important to better know the characteristics of the materials to be used. In this context, stands out the subgrade, the foundation for the whole structure of the pavement, which one is studied in the present reseach by considering three typical soils used as highway subgrade in Santa Maria, Rio Grande do Sul State, and having the permanent deformations as the main focus. The metodology aplied in this work consisted in the location, sampling and characterization of the soil fields, lab tests and empirical machanistic design. Besides the physical, chemical and mechanical characterizations, it was performed the repeated triaxial load test aiming to obtain the resilient modulus and the permanent deformation parameters, according to the Brazilian Petroleum Corporation Manual (PETROBRAS). The Resilient Modulus model presented the better results with frequencies of 1 Hz and 2 Hz, and the presence of silt in one of the soils affected its resilient behaviour. The permanent deformation tests were performed with the frequency of 2 Hz and 150.000 load cicles. The average statistic correlation, according to Guimaraes (2009)´s methodology, was 0.91, bigger than the one provided by the Monismith and Barksdale´s models. However, the dominance of fine grained soils, along with low compactation energy, lead to a higher deformation rates, motivating the use of intermediate energy. With this new approach the permanent deformation was reduced 40% and the resilient modulus increased 78,8%. However, the numerical simulation according to the mechanistic approach, and using the layer thickness obtained from the Departamento Nacional de Infraestrutura de Transportes (DNIT) method, under 8,2 ton standard axle load, showed that the wheel tracks deeping would be small, based on the low stresses observed in the subgrade. On the other hand, the fatigue behaviour presented an inferior performance, reducing the project´s useful life. It was observed the presence of shakedown in the ranges A, B and C.